The processes for making and unmaking of interregional boundaries in the Ethiopian federation - Bekele Lemi Deressa (Cogent Social Sciences, 2024)
This article analyzed the processes of (un)making interregional boundaries and described the actors in the Ethiopian federation going back to the Transitional Period. It employed interview and document analysis to organize the data collected. For interview purpose, liberation fronts’ representatives and political party leaders, as well as professionals in the field of federalism were selected purposively because of their life experiences and exposure to the field. The data was analyzed qualitatively using content analysis, and secondary data obtained from secondary sources were meticulously reviewed and triangulated to ensure that the primary data were as valid as possible. It found out that since 1991, Ethiopia has passed through at least four phases of the (un)making processes. It started with making 14 National/Regional Self-Governments in 1992. The motives of the liberation movements, data collected by the Institute of Nationalities, the borders of Woredas, and ‘forceful’ amalgamation are among of the guiding principles identified in the study. The Transitional Period Boundary Commission, liberation movements/fronts, etc. were found to be the major actors involved in the (un)making processes. Currently, 12 regions exist and additional region(s) may emerge in the future. The (un)making of constituent units undertaken so far imply that such trends can contain some recurring claims, but may not resolve it in a sustainable way. It should be understood that federalism is a working progress, not a onetime panacea.